EFFECTS OF DRILL AND PRACTICE INSTRUCTIONAL STRATEGY ON SENIOR SECONDARY SCHOOLS STUDENTS’ MATHEMATICAL SKILLS IN PHYSICS IN EKITI STATE, NIGERIA - Alaba Lawrence Aladejana; Joseph Oba Fatoba (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This study focused on the effect of drill and practice instructional strategies on students’ mathematical skills in Physics. The pretest posttest control group quasi-experimental research design was employed. The sample size for this study was sixty five (65) Senior Secondary School II physics students was used in this study. Physics Mathematical Skills Test of twenty (20) items multiple choice type questions was used to collect the data. Analysis of covariance (ANCOVA) and Analysis of variance (ANOVA) were used to analysed the data collected. The findings of the study revealed that there was no significant effect of the treatment on students’ mathematical skills and there was also no significant effect of gender on students’ mathematical skills in physics. Based on the findings of the study, it was therefore recommended that Physics teachers, though drill and practice instructional strategy has no effect on students mathematical skills, should endeavour to employ drill and practice strategy with conventional method in the teaching and learning process due to its advantages.